2004
DOI: 10.5650/jos.53.471
|View full text |Cite
|
Sign up to set email alerts
|

Lipase-Catalyzed Synthesis of Palm-Based Wax Esters

Abstract: Wax esters are long chain esters that are derived from long chain fatty acids and long chain alcohols with chain lengths of 12 carbons or more. The compounds have many potential applications. The present work focuses on the synthesis of wax esters by alcoholysis of palm oil with oleyl alcohol using Lipozyme. The effects of various reaction parameters such as reaction time, temperature, amount of enzyme, molar ratio of substrates, various organic solvents and initial water activity (a w ) of the reaction system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 18 publications
3
33
0
4
Order By: Relevance
“…The optimal PO/OA ratio for the alcoholysis reaction is 3:1. Similar result was obtained in the laboratory scale synthesis (19). Steinke et al (2001) reported that lipase-catalyzed esterification of stoichiometric mixtures of long-chain and very long-chain fatty acids with the corresponding mixture of alcohols gave quantitative yields of wax esters (28).…”
Section: Optimization Of Reactionsupporting
confidence: 81%
See 2 more Smart Citations
“…The optimal PO/OA ratio for the alcoholysis reaction is 3:1. Similar result was obtained in the laboratory scale synthesis (19). Steinke et al (2001) reported that lipase-catalyzed esterification of stoichiometric mixtures of long-chain and very long-chain fatty acids with the corresponding mixture of alcohols gave quantitative yields of wax esters (28).…”
Section: Optimization Of Reactionsupporting
confidence: 81%
“…Glycerol will be accumulated and may inhibit the reaction by limiting the interaction of the substrate and the enzyme (21). Previous work reported by Gunawan et al (19) in the laboratory scale study also showed that alcoholysis conversion from palm oil reached up to 85% in 300 min, with Lipozyme RM IM as the biocatalyst (19). Hence, 300 min was chosen as the optimum reaction time in this study while varying other variables in the RSM design.…”
Section: Effect Of Reaction Timementioning
confidence: 95%
See 1 more Smart Citation
“…Among of the works are syntheses of esters from palm oil. Alcoholysis of triglycerides from palm oil to produce palm oil esters using lipase as a catalyst is a relatively simple process and moreover the starting materials are cheap [3][4][5][6] . Synthesis or modification of lipids for example; modification of Palm Oil into Palm Oil Esters (POEs) has grown due to the possibility of obtaining a wide variety of high quality natural products under mild reaction conditions utilizing selective enzyme substrate as environment friendly biocatalysts 2,7) .…”
Section: Introductionmentioning
confidence: 99%
“…shows that hexane (log-P= 3.5) was the best solvent for amidolysis of palm olein due to the reaction medium was changed from hydrophilic (log-P < 3) to hydrophobic (log-P > 3) organic solvents, the overall efficiency of the enzyme changed 20) . Therefore, hexane was choose the solvent in the subsequent experiments.…”
mentioning
confidence: 99%